Hidrogênio verde: seu papel estratégico na transição energética - Garcia, Gessika da Silva (Universidade Federal de São Carlos, 2024)
The search for more ecological and efficient energy sources has increased, driven by growing global demand. Despite the increase in the capabilities of renewable sources, such as wind and solar energy, it has become crucial to diversify options in the face of the continuous increase in demand. The current scenario, marked by intensification of global warming and the energy crisis in Europe, highlights the urgent need to reduce greenhouse gas emissions. The global context, marked by energy crises and climate change, highlights the urgency of the transition to cleaner sources. This work explores the potential of Green Hydrogen as a strategic solution, highlighting its production through electrolysis using the sources already mentioned and their role in decarbonization. The purpose of this work is to approach a macro-analysis, which allows discussing, visualize and reflect the potential of Green Hydrogen as a strategic alternative in promoting decarbonization, especially in the industrial and transport sectors. The objective is to contribute to the understanding of the implications and potential benefits associated with transitioning to green hydrogen as an alternative viable and sustainable alternative to fossil fuels. All of this happens within the context of the current global environmental sustainability agenda, which is moves towards commitment to mitigating environmental impacts and the promotion of more environmentally responsible energy sources. The monograph addresses possible feasibility, present challenges and the socioeconomic impact of this energy potential. The panorama of projects in the world and Brazil's positioning as a possible future exporter of this new energy source. Gives visibility to the technical challenges, but lists the advantages that elucidate Brazil's potential to lead this global movement. The work culminates in critical reflections on the disposition of hydrogen green in the energy transition, ending with final considerations that envision a challenging but promising future for its integration into the energy matrix global. Keywords: Green Hydrogen; Carbon Dioxide Emission; It is made Stove; Clean energy; Fuel Cells; Energy Transition.
Green hydrogen: its strategic role in energy transition
Keywords: Hidrogênio verde; Emissão de dióxido de carbono; Efeito estufa; Energia limpa; Células de combustível; Transição energética; Green hydrogen; Carbon dioxide emission; Greenhouse effect; Clean energy; Fuel Cells; Energy transition; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA